2050 - tomorrow's tourism - Yeoman, Ian; Rebecca, Tan Li Yu; Mars, Michelle; Wouters, Mariska (Aspects of tourism, 2012)
This book constructs scenarios from Shanghai to Edinburgh, Seoul to California encompassing complex topics such as human trafficking, conferences, transport, food tourism or technological innovation. This is a blue skies thinking book about the future of tourism and a thought-provoking analytical commentary.